Repurposing the prostaglandin analogue treprostinil and the calcium-sensing receptor modulator cinacalcet to revive cord blood as an alternate source of hematopoietic stem and progenitor cells for transplantation - Prchal-Murphy, Michaela; Zehenter, Julia; Fischer, Marlene; Pirabe, Anita; Themanns, Madeleine; Afrashteh, Behnaz; Putz, Eva Maria; Kollmann, Karoline; Basílio, José; Salzmann, Manuel; Strohmaier, Wolfgang; Krumpl, Günther; et al. (Frontiers in Pharmacology, 2025)
ObjectiveThe expanding field of hematopoietic cell transplantation (HCT) for non-malignant diseases, including those amenable to gene therapy or gene editing, faces challenges due to limited donor availability and the toxicity associated with cell collection methods. Umbilical cord blood (CB) represents a readily accessible source of hematopoietic stem and progenitor cells (HSPCs); however, the cell dose obtainable from a single cord blood unit is frequently insufficient. This limitation can be addressed by enhancing the potency of HSPCs, specifically their capacity to reconstitute hematopoiesis. In our study, we investigated the combined effects of treprostinil, a prostaglandin analog, and cinacalcet, a calcium-sensing receptor modulator, on the reconstitution of hematopoiesis.MethodsA Lineage Cell Depletion Kit was employed to isolate lineage-negative (lin−) HSPCs from mouse bone marrow. A Human CB CD34 Positive Selection Kit was utilized to isolate CD34+ cells from the CB of healthy donors. In vitro, the effects of treprostinil, cinacalcet, and their combination on the migration, adhesion, and differentiation of HSPCs were assessed. In vivo, homing and engraftment were examined. Eight-week-old female and male C57BL/6J, BALB/c, or female NSG mice served as recipient models.ResultsWhen administered concomitantly, treprostinil and cinacalcet exhibited mutual antagonism: the survival of recipient animals was lower when both drugs were administered together compared to either agent alone. Conversely, a sequential regimen involving priming with treprostinil/forskolin followed by cinacalcet treatment in vivo enhanced survival, irrespective of whether hematopoiesis was reconstituted by human or murine HSPCs. In vitro assays demonstrated enhanced migration and adhesion in response to the presence of treprostinil and cinacalcet, suggesting potential synergistic effects. Colony formation confirmed synergism.ConclusionAugmenting the bone marrow reconstitution potential of HSPCs with treprostinil and cinacalcet shows promise for rescuing patients undergoing HCT. This approach is particularly beneficial for those patients at high risk of transplant failure due to limited numbers of available HSPCs. Furthermore, enhancing the potency of HSPCs has the potential to alleviate the burden and risks associated with HSPC donation, as it would reduce the number of cells needed for collection.